Analisis Asas Keseimbangan dalam Kewajiban Penyediaan Fasilitas Umum dan Fasilitas Sosial di Perumahan Lampung Utara - Siti Nazwa Aprilisia (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
Housing development is not solely aimed at providing housing, but must also ensure the provision of public and social facilities as part of consumers' rights to a decent living environment. This study aims to examine the application of the principle of balance in housing purchase agreements, specifically regarding developers' obligations to provide public and social facilities, and to analyze the legal implications of failure to fulfill these obligations in North Lampung Regency. This study uses a normative legal research method with a statutory and conceptual approach, supported by primary and secondary legal materials, and then analyzed qualitatively. The results indicate that the principle of balance in housing purchase agreements has not been optimally implemented, primarily due to the dominance of developers through the use of standard agreements that weaken consumers' bargaining power. The failure to provide public and social facilities, as occurred in the Matrix Sukajadi Housing Complex, reflects an imbalance between the rights and obligations of the parties. Legally, this developer's negligence can be classified as a breach of contract and a violation of the principles of fairness in contracts and consumer protection. Therefore, strengthening the supervisory role of local governments and consistent law enforcement are crucial to ensuring consumer protection and realizing equitable and sustainable housing provision.